2001
DOI: 10.1046/j.1365-201x.2001.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin synthesis and receptors in porcine kidney

Abstract: As insufficient information on the endothelin (ET) system in the porcine kidney is available at present, we investigated renal ET-1 synthesis and ET receptors in this species. Because ET specifically affects renal and glomerular haemodynamics and distal tubular reabsorption, we studied ET-1 synthesis in isolated glomeruli and in inner medullary collecting duct (IMCD) cells and preproET-1 mRNA in renal cortex, isolated glomeruli and papillary tissue. In addition, we characterized density and properties of ET re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…As for ET-1 production, the highest binding of ET-1 is in IMCD, followed by OMCD and CCD (88). ETB is the major ET receptor isoform expressed by the CD in experimental animals and humans (3,12,40,51,88,90,102). Although more difficult to demonstrate, CD also express ETA (11,18,45,65,102,113).…”
Section: Expression and Regulation Of Collecting Duct Et Receptorsmentioning
confidence: 92%
“…As for ET-1 production, the highest binding of ET-1 is in IMCD, followed by OMCD and CCD (88). ETB is the major ET receptor isoform expressed by the CD in experimental animals and humans (3,12,40,51,88,90,102). Although more difficult to demonstrate, CD also express ETA (11,18,45,65,102,113).…”
Section: Expression and Regulation Of Collecting Duct Et Receptorsmentioning
confidence: 92%
“…Descending vasa recta in the outer medulla express both ET A and ET B . In the porcine kidney, the relative ET A /ET B proportion averaged ~60/40 in glomerular membranes, but only ET B binding could be identified in papillary membrane preparations (25). Similar studies conducted using human tissues suggest that ~30% of the receptors expressed in both the renal cortex and medulla are of the ET A subtype (529).…”
Section: Endothelin and The Kidneymentioning
confidence: 99%
“…Metabolic labeling, immunohistochemical and radioimmunoassay analysis of ET levels, as well as RT-PCR of mRNA expression in microdissected nephron segments have repeatedly shown that the inner medullary CD (IMCD) produces more ET (primarily ET-1) than any other cell type in the nephron, at least in the rat and rabbit (97, 368, 787, 790). Similarly, porcine IMCD synthesize relatively high levels of ET-1 (25). These findings were further supported by in situ hybridization studies of human kidneys (598); in addition, ET-1 release and mRNA expression have been detected in cultured human IMCD cells (367).…”
Section: Endothelin and The Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…Descending vasa recta in the outer medulla express both ETA and ETB. The relative ETA/ETB proportion in porcine kidneys averages approximately 60/40 in glomerular membranes, but only ETB binding could be identified in papillary membranes (19). Approximately 30% of the receptors expressed in the human renal cortex and medulla are ETA (300).…”
Section: Et and The Renal Vasculaturementioning
confidence: 99%